ANALYSIS OF COAL COMBUSTION ENERGY CALCULATION BASED ON COAL CAVITY PHYSICAL MODEL OF UNDERGROUND COAL GASIFICATION TESTING IN LABORATORY SCALE - Rukyat Fauzi, Faqrin
Most of Indonesia's coal resources are low-calorie coal and have a depth of more than 100 meters. Utilization of coal is still done in a conventional way, both by the open-pit method and underground mining. Underground Coal Gasification (UCG) can be one alternative to exploit the potential of Indonesian coal amid the increasing global energy demand, although environmental aspects are still an important concern in the application of this technology. One of the environmental impacts due to the application of Underground Coal Gasification (UCG) technology is a decrease in the land surface caused by cavities formed during the underground gasification process. In addition, the combustion energy in the process of forming coal cavities has a relationship to the characteristics of gas products resulting from the gasification process. This study aims to determine the effect of temperature and injection flow rate of oxygen and compressed air on coal cavities formation of Underground Coal Gasification testing in laboratory scale. The results showed that, at high temperature, the coal cavities formed increases. In addition, the injection flow rate of oxygen and compressed air can improve coal cavities formed. This is indicated by the rate of cavity formation at the injection stage having a higher value than at the initial combustion stage. The quality of gas products in this study has decreased in the final stages of testing. The gas products in the 50th minute had CH4, CO2, and CO concentrations of 351.39 ppm; 149.55 ppm; and 10,100.70 ppm. Whereas the gas products in the 60th minute had CH4, CO2, and CO concentrations of 105.08 ppm; 257.52 ppm; and 526.31 ppm. The decline in the quality of the gas product is influenced by the decrease in the reactivity rate determined from the coal combustion energy through the physical model of the formed coal cavity.